Interrelation Between the Changes of Phase Functions of Cardiac Muscle Contraction and Biochemical Processes as an Algorithm for Identifying Local Pathologies in Cardiovascular System - Fedosov, Yury; Zhigalov, Stanislav; Rudenko, Mikhail; Zernov, Vladimir; Voronova, Olga (IntechOpen, 2012)
None